Tapping to Music Predicts Literacy Skills of First-Grade Children - Kertész, Csaba; Honbolygó, Ferenc (Frontiers in Psychology, 2021)
The ability to synchronize one’s movements to the sound of a regular beat has been associated with children’s language and reading abilities. Sensorimotor synchronization, or tapping performance can among other factors (e.g. working memory and RAN) predict phonological awareness and word reading accuracy and fluency of first graders. While tapping tasks that use a simple metronome sound are more often used, applying musical stimuli has the potential advantage of being more engaging and motivating for children. In the present study, we investigated whether tapping to a metronome beat or complex musical stimuli would predict phonological awareness and reading outcomes of Hungarian 6-7 year-olds (N=37). We also measured participants’ general cognitive abilities (RAN, non-verbal intelligence and verbal working memory). Our results show that phonological awareness, spelling and reading accuracy were associated with the musical tasks while reading fluency was predicted by the metronome trials. Our findings suggest that complex musical tasks should be considered when investigating this age group, as they were, in general, more effective in predicting literacy outcomes.